2004
DOI: 10.1242/jcs.01358
|View full text |Cite
|
Sign up to set email alerts
|

The role of myosin heavy chain phosphorylation in Dictyostelium motility, chemotaxis and F-actin localization

Abstract: To assess the role of myosin II heavy chain (MHC) phosphorylation in basic motility and natural chemotaxis, the Dictyostelium mhcA null mutant mhcA-, mhcA- cells rescued with a myosin II gene that mimics the constitutively unphosphorylated state (3XALA) and mhcA- cells rescued with a myosin II gene that mimics the constitutively phosphorylated state (3XASP), were analyzed in buffer and in response to the individual spatial, temporal and concentration components of a cAMP wave using computer-assisted methods. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…This hypothesis is supported by the observation that cells lacking the Aimless RasGEF or the Ras effector RIP3 display a significantly reduced chemoattractantinduced cGMP response, although it is unclear if this effect is direct or indirect [112]. Furthermore, rip3-null cells exhibit a marked polarization defect, migrate more slowly than wild-type cells and extend lateral pseudopodia during chemotaxis, which is reminiscent of cells lacking myosin II (mhcA − cells) [125,128]. Consistent with the involvement of Ras in guanylate cyclase activation, a recent study indicates that cells lacking either RasG or RasC display reduced cAMP-induced cGMP production, whereas cells that lack both Ras proteins completely fail to produce a cGMP response [34].…”
Section: Regulation Of Actin-myosin Assemblymentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is supported by the observation that cells lacking the Aimless RasGEF or the Ras effector RIP3 display a significantly reduced chemoattractantinduced cGMP response, although it is unclear if this effect is direct or indirect [112]. Furthermore, rip3-null cells exhibit a marked polarization defect, migrate more slowly than wild-type cells and extend lateral pseudopodia during chemotaxis, which is reminiscent of cells lacking myosin II (mhcA − cells) [125,128]. Consistent with the involvement of Ras in guanylate cyclase activation, a recent study indicates that cells lacking either RasG or RasC display reduced cAMP-induced cGMP production, whereas cells that lack both Ras proteins completely fail to produce a cGMP response [34].…”
Section: Regulation Of Actin-myosin Assemblymentioning
confidence: 97%
“…The assembly of actin-myosin filaments is suggested to stabilize the actin cytoskeleton and consequently enhance cortical rigidity, as well as to provide the motor activity necessary for efficient cell migration, through the ATP-driven translocation of actin filaments [124]. Myosin II localizes to the sides and rear of chemotactic neutrophils and Dictyostelium cells, where it prevents the formation of lateral pseudopodia and promotes cell-body contraction and posterior retraction [50,[125][126][127][128][129]. Despite its conserved role, myosin II appears to be differently regulated in mammalian and Dictyostelium cells [123,124,130].…”
Section: Regulation Of Actin-myosin Assemblymentioning
confidence: 99%
“…However, Wessels et al found that pten -cells are defective in myosin II assembly at the cell cortex in response to chemoattractant, providing insight into the possible mechanism underlying the lack of repression of lateral pseudopodia in these cells (Wessels et al, 2007). Indeed, myosin II normally localizes to the sides and rear of chemotactic neutrophils and Dictyostelium cells, where it prevents the formation of lateral pseudopodia and promotes cell body contraction and posterior retraction (Heid et al, 2005;Heid et al, 2004;Stites et al, 1998;Uchida et al, 2003;Wessels et al, 1988;Xu et al, 2003). Given its sequence similarity to the actin-binding protein tensin, Wessels et al further suggest that PTEN could directly interact with and modulate the F-actin-myosin cytoskeleton, implying that PTEN could play a role in cytoskeleton regulation that is independent of its PtdIns(3,4,5)P 3 phosphatase activity.…”
Section: Chemotaxis In the Absence Of Pi3k And/or Ptenmentioning
confidence: 99%
“…formation, as it had been demonstrated to play a role in cell locomotion, responsiveness to chemotactic signals and, most importantly, pseudopod formation Heid et al, 2004). The three mutant cell lines were HS1, an MHC-null mutant (Manstein et al, 1989), 3XALA, in which the three threonine phosphorylation sites of MHC are replaced with alanine so that it mimics the constitutively unphosphorylated state (Egelhoff et al, 1993;Egelhoff et al, 1996), and 3XASP, in which the three threonine phosphorylation sites of MHC are replaced with aspartate residues so that it mimics the constitutively phosphorylated state (Egelhoff et al, 1993).…”
mentioning
confidence: 99%